EVALUATION OF BIOLOGICAL NITROGEN FIXATION (BNF) AND GREEN MANURE POTENTIAL OF SOME FORAGE LEGUMES - Bashir, A.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
A pot experiment was conducted in 2013 rainy season at the Screen house, Faculty of Agriculture, University of Maiduguri to evaluate biological nitrogen fixation (BNF) and green manure potentials of some forage legumes. The experiment consisted of 8 forage legumes – Mucuna pruriens white(T2), Stylosanthesis guianensis(T3), Cajanus cajan brown(T5), Cajanus cajan white(T7), Centrosema pubscens(T9), Lablab purpereus white(T11), Lablab purpereus black(12) and sesbania rostrata(15). The plants were grown for six weeks, then roots and above ground fresh biomass weighed. Percent N, P, and K content were determined in the laboratory. The result showed Mucuna, Sesbania, Cajanus cajan, Stylosanthesis and Lablab were the top N2-fixers with 23.88, 14.27, 13.78, 13.58 and 9.18 kg/ha respectively. Therefore, above top N-fixers were recommended for use as green manure in the cropping systems of the region.